Iraqi legislation and its impact in reality The current developmental economist - المياحى, عمــــار فــــوزي (Journal of Legal Sciences, 2020)
The economic problems of external debt were illustrated by the impact of increased external borrowing on the faltering of economic development efforts by the impact of external loans on domestic savings, the balance of payments, their impact on inflation, the growing economic dependency abroad, the loss of national economic decision-making, The rise in the ratio of external debt to GDP, and fiscal deficits in a vicious cycle.As we are found in the economies of the different states, there are mostly many problems that happen to peoples causing them to be poor and tied, that is when the states resort to borrowing from the national banks and selling the bonds and treasury bonds and claiming donations and gifts and other trials for solving the crisis, but finally if it finds no alternative but resorting to borrowing from outside.The International Monetary Fund and its regulatory system, as one of the institutions resulting from the Bretton Woods Agreement in 1944, are accompanied by the International Bank for Reconstruction and Development (IBRD), its voting power, the weight of developing countries in these forces, its reflection on decision-making within the IMF and the latest developments in lending, In its oversight of the economic policies of member countries, IMF's interest in total expenditure (and its core components such as consumer spending and business investment), output, employment and inflation, as well as the country's balance of payments - its balance of transactions with du For the outside world.